Rancang Bangun Sistem Informasi Penjualan Online (E-Commerce) Pada Toko Batik Pekalongan Dengan Metode Waterfall - Nia Nuraeni; Puji Astuti (Universitas Bina Sarana Informatika, 2019)
Pekalongan Batik is a typical batik originating from Central Java Pekalongan, Pekalongan batik has been well known in various regions in Indonesia. Nowadays batik is an Indonesian culture so every company or government institution requires using batik on one day during their working hours. Pekalongan batik producers in Central Java, of course, have difficulty in marketing their products, especially marketing outside Central Java. E-Commerce is one of the solutions to these problems. Internet networks that are not limited to space and time can of course make it easier for manufacturers to market their products. E-Commerce is the best solution, as a marketing and promotional media for Pekalongan batik by anyone, anywhere and anytime. Use of PHP programming language, SQL database and adobe Dreamweaver application is used to design this online sales website with the SDLC (Systems Development Life Cycle) method in applying the website creation method